Morphological and molecular identification of Schizophyllum commune causing storage bulb rot disease of Lanzhou edible lily in China and its biological characteristics - Liang, Qiaolan; Wei, Liexin; Chen, Ying’e; Xu, Bingliang; Zhang, Na (Frontiers in Microbiology, 2024)
Lily bulb rot disease has harmed edible lily in recent years, resulting in yield losses in China. As a results, both morphological and molecular techniques must be used to confirm the etiology of storage bulb rot disease on lily bulbs. Lily bulbs with indications of rot symptoms during storage were gathered in Lanzhou, Gansu Province, China. A strain was isolated and its morphologically characterized as a Schizophyllum commune specie. Pathogenicity tests further confirmed that the strain caused apparent S. commune symptoms on lily bulbs which were consistent with those seen in the field. The pathogenicity of S. commune to lily bulb was 100%, and morphological identification showed that the mycelia of the pathogen were white and villous, with septate, branched, and acicular bodies and obvious lock-shaped joints. The mycelia had uneven thickness, ranging from 1.03 to 3.06 μm, and turned gray-white at the later growth stage. Moreover, the pathogen formed a mycelial column on potato dextrose agar (PDA) medium, which formed a coral-like fruiting body primordium, which split, forming pileus for spore production. The spores were colorless and cylindrical, with an oblique tip and a size of 4.6–7.2 μm × 2.2–2.7 μm. The isolate was deduced as based on phylogenetic analysis with 2 genes (ribosomal DNA-ITS and LSU) as well as morphological characteristics and cultural features, the isolate was identified S. commune. Soluble starch, yeast extract, temperature of 30°C, pH 7, relative humidity of 100%, and complete dark were shown to be the optimum culture conditions for surface mycelium growth. In conclusion, this is the first report of S. commune causing bulb rot of edible lilies in China. The study provides a basis for more effective control strategies for lily bulb rot disease.